EFEKTIVITAS PENERAPAN SOFTWARE AKUNTANSI TERHADAP LAPORAN KEUANGAN UMKM HALAL BOGOR - Reza, Annisa Fadhilah; Febraini, Dewi (Islamic Economics Program, Faculty of Islamic Economics and Business, 2024)
Optimal financial report quality is when the report provides significant benefits and meets all expected qualitative characteristics. It is noted that a high frequency of transactions occurs in Small and Medium Enterprises. It is also not easy for them to record transactions. Previous studies have shown that the utilization of accounting software in MSMEs is necessary to improve the timeliness and timely and accurate financial statements. In Bogor City, improving the quality of financial reports in MSMEs is inseparable from the City Government's efforts in implementing the applicable Financial Accounting Standards (SAK) and Government Accounting Standards (SAP), by utilizing accounting information systems. The implementation of these information systems is an important step in ensuring quality financial reports, given the importance of public accountability in government financial reporting. By using the DeLone and McLean Information Systems Success Model method as well as a quantitative descriptive approach and Structural Equation Modeling Partial Least Squares (SEM PLS), primary data were collected through questionnaires addressed to Halal MSMEs in Bogor City. The results showed that system quality did not have a significant impact on perceived benefits. Likewise, information quality has no effect on perceived benefits. System quality also has no significant impact on end-user satisfaction; however, information quality is shown to make a positive contribution to end-user satisfaction. Nonetheless, perceived benefits did not have a positive impact on end-user satisfaction. End-user satisfaction, in turn, had a significant influence on system usage.